2013
DOI: 10.1021/np400683h
|View full text |Cite
|
Sign up to set email alerts
|

Phenylspirodrimanes with Anti-HIV Activity from the Sponge-Derived Fungus Stachybotrys chartarum MXH-X73

Abstract: Seven new phenylspirodrimanes, named stachybotrins D-F (1, 3, 4), stachybocins E and F (5, 6), and stachybosides A and B (7, 8), and four known compounds (2, 9-11), were isolated from the sponge-derived fungus Stachybotrys chartarum MXH-X73. Their structures were determined by detailed analysis of spectroscopic data. The absolute configurations of 1-8 were determined by chemical hydrolysis and modified Mosher's and Marfey's methods. All compounds were tested in an anti-HIV activity assay, and compound 1 showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 42 publications
0
57
0
1
Order By: Relevance
“…Park and colleagues reported that two polybromocatechol compounds ( 99 , 100 ), isolated from the red alga Neorhodomela aculeate , inhibited infection and cytopathic effects on a HeLa cell line by HRV2 and HRV3, causal agents of viral respiratory infections and common colds [99]. Ma and colleagues determined that the novel phenylspirodrimane stachybotrin D ( 101 ), isolated from the fungus Stachybotrys chartarum MXH-X73 derived from the Chinese marine sponge Xestospongia testudinaria , inhibited HIV-1 replication of wild-type and five non-nucleoside reverse transcriptase inhibitor (NNRTI)-resistant HIV-1 strains by inhibiting the reverse transcriptase, and thus “provides a new class of chemotype for the search of NNRT inhibitors” [100]. Jiao and colleagues reported that streptoseolactone ( 102 ), derived from the actinomycete Streptomyces seoulensis strain isolated from the shrimp Penasus orientalis , inhibited neuraminidase by a noncompetitive mechanism, a finding “of value in terms of drug discovery for the treatment of influenza” [101].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Park and colleagues reported that two polybromocatechol compounds ( 99 , 100 ), isolated from the red alga Neorhodomela aculeate , inhibited infection and cytopathic effects on a HeLa cell line by HRV2 and HRV3, causal agents of viral respiratory infections and common colds [99]. Ma and colleagues determined that the novel phenylspirodrimane stachybotrin D ( 101 ), isolated from the fungus Stachybotrys chartarum MXH-X73 derived from the Chinese marine sponge Xestospongia testudinaria , inhibited HIV-1 replication of wild-type and five non-nucleoside reverse transcriptase inhibitor (NNRTI)-resistant HIV-1 strains by inhibiting the reverse transcriptase, and thus “provides a new class of chemotype for the search of NNRT inhibitors” [100]. Jiao and colleagues reported that streptoseolactone ( 102 ), derived from the actinomycete Streptomyces seoulensis strain isolated from the shrimp Penasus orientalis , inhibited neuraminidase by a noncompetitive mechanism, a finding “of value in terms of drug discovery for the treatment of influenza” [101].…”
Section: Marine Compounds With Antibacterial Antifungal Antiprotmentioning
confidence: 99%
“…Thus, the substitution of a Cl-atom at the methine C(11) was supposed. 2) assigned C(10) and C (12) to be in (R)-and (S)-configuration, respectively. Based on the modified Mosher's method for n-diols by NMR data [14], the Dd (d Rd S ) values of the methoxyphenylacetic acid (MPA) esters of 1 were calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The linkage of the pentane unit to C(3) (d(C) 155.2) was assigned by the HMBC interaction from H-C(4) (d(H) 6.57) to C(9) (d(C) 39.0) and C (10). The coupling constants (J(10,9a) = 4.2 Hz, J(10,9b) = 8.9 Hz, J(10,11) = 4.0 Hz, J (11,12) = 8.2 Hz) reflected gauche relationship between H-C(10)/H a -C(9) and H-C(10)/H-C(11), and antiorientation between H-C(10)/H b -C(9) and H-C(11)/H-C (12). The positive Dd data of H-C(10) (+0.098) and CH 2 (9) (+0.6942, +0.4783) and the negative Dd data of H-C(12) (À0.4114) and Me(13) (À0.6248) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites M1, M2-9, M3-1, M3-2, M5-2, M5-3, M5-4, and M5-5 were screened for their activities against HIV-1 using pseudotyped viruses as described previously (Ma et al, 2013). Briefly, VSV-G/HIV-1 viruses were prepared by co-transfecting 293T cells with VSV-G plasmid and env-deficient HIV-1 vector (pNL4-3.luc.R-E-, Supplemental Figures S1, S2).…”
Section: Methodsmentioning
confidence: 99%